Transanal Hemorrhoidal Dearterialization (THD) Anolift-Prospective Assessment of Safety and Efficacy - Giordano, Pasquale; Schembari, Elena (Frontiers in Surgery, 2021)
The adjunct of a mucopexy to conventional dearterialization has become a routine part of the transanal hemorrhoidal dearterialization procedure in order to facilitate the management of the prolapsing component and has helped to expand the indications of this technique to more advanced stages of hemorrhoidal disease. A simple technical modification of THD with targeted mucopexy (TM), called Anolift, is described. The aim of the study was to evaluate the safety and effectiveness of this technical variation. The procedure consisted of two parts: one aimed at the dearterialization and the other concentrated on the management of the prolapsing component. Once all the arteries were identified and transfixed an Anolift targeted mucopexy was performed using a continuous barbed suture with a synthetic absorbable monofilament (Polydioxanone) 2/0 Filbloc (Assut Europe) stitch mounted on a 4/8 30 mm needle. Severity of hemorrhoidal symptoms was scored from 0 to 20 using a dedicated questionnaire: the Hemorrhoidal Assessment Severity Score (HASS). From May 2018 to November 2020, 60 patients with hemorrhoidal disease (HD) underwent a THD Anolift procedure. Three patients experienced severe post-operative pain and 10 (23%) suffered with difficulty in evacuation. The median follow-up period was 15.5 months (range 2–32 months). The mean HASS changed from 16.43 pre-operatively to 1.95 post-operatively (p < 0.0001). Pre-operative HASS very strongly correlated with the degree of hemorrhoids (p < 0.001), while there was no correlation between the pre-operative HASS or the degree of hemorrhoids and the post-operative HASS (p = 0.163). There was no significant difference in predicted post-operative HASS according to the pre-operative HD stage. One patient (1.6%) with circumferential IV hemorrhoids had a recurrence and required a further THD. Two patients had excision of skin tags (3%). The Anolift technique is safe and effective for the management of HD even in patients with advanced stages.